2007
DOI: 10.1099/mic.0.2007/009340-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronological and replicative life-span extension in Saccharomyces cerevisiae by increased dosage of alcohol dehydrogenase 1

Abstract: Alcohol dehydrogenase 1 (Adh1)p catalyses the conversion of acetaldehyde to ethanol, regenerating NAD + . In Saccharomyces cerevisiae, Adh1p is oxidatively modified during ageing and, consequently, its activity becomes reduced. To analyse whether maintaining this activity is advantageous for the cell, a yeast strain with an extra copy of the ADH1 gene (2¾ADH1) was constructed, and the effects on chronological and replicative ageing were analysed. The strain showed increased survival in stationary phase (chrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Schurig-Briccio et al (43) demonstrated enhanced RoS level in stationary phase cell of Escherichia coli during conditions of endogenous and exogenous oxidative stress. the same relationship between oxidative stress and RoS generation has been found in different fungal strains (16), yeasts (28,33,41) and bacteria (31).…”
Section: At Cold Temperaturessupporting
confidence: 71%
“…Schurig-Briccio et al (43) demonstrated enhanced RoS level in stationary phase cell of Escherichia coli during conditions of endogenous and exogenous oxidative stress. the same relationship between oxidative stress and RoS generation has been found in different fungal strains (16), yeasts (28,33,41) and bacteria (31).…”
Section: At Cold Temperaturessupporting
confidence: 71%
“…A standard curve containing serial dilutions of a reference extract was used to estimate the relative SOD activity in each extract. Oxygen Consumption-Oxygen consumption was measured in a Clark detector as described (31). In brief, oxygen uptake was measured in a 4-ml stirred chamber (100 rpm) using a YSI model 53 biological oxygen monitor (Yellow Springs Instruments) following the manufacturer's directions.…”
Section: Methodsmentioning
confidence: 99%
“…The dihydroethidium (Fluka) oxidation rate was performed as described (36). Oxygen consumption was measured in a Clark detector as described (37 …”
Section: Methodsmentioning
confidence: 99%